Prevalence of Blastocystis infection in free-range Tibetan sheep and Tibetan goats in the Qinghai-Tibetan Plateau in China - Yankai Chang (Elsevier, 2021)
Blastocystis is one of the most common enteric parasites in humans and domestic animals. For Tibetan sheep and Tibetan goats, the traditional grazing methods still occupy a dominant position, and the close contact between humans and domestic animals increases the risk of infection by Blastocystis between herdsmen and livestock. However, less pertinent information is available for Tibetan sheep or Tibetan goats. In this study, 880 fecal specimens from Tibetan sheep and Tibetan goats were collected from 6 sampling sites in Tibet to test for Blastocystis using the polymerase chain reaction and sequencing analysis of the partial SSU rRNA gene. The infection rate of Blastocystis was 8.55% for Tibetan sheep (53/620) and 8.46% for Tibetan goats (22/260). The genetic analysis of 53 positive samples from Tibetan sheep identified 4 known subtypes (ST4, ST5, ST10, and ST14). Four known subtypes (ST1, ST5, ST6, and ST10) were identified in Tibetan goats. ST10 was the dominant subtype in Tibetan sheep and Tibetan goats, accounting for 65.33% (49/75) of total subtypes. ST1, ST4, ST5, and ST6 were recognized as belonging to zoonotic subtypes. This report provides a detailed data on the prevalence and subtype distribution of Blastocystis in Tibetan sheep and Tibetan goats in Tibet, which enriches the epidemiological data of Blastocystis infection in Tibetan sheep and Tibetan goats in China. Our results indicated that Tibetan sheep and Tibetan goats can be infected with multiple Blastocystis subtypes, including zoonotic subtypes. More research is needed among humans, livestock and wild animals in Tibet to better understand their role in the spread of Blastocystis. And, One Health measures need to be taken to control and prevent its zoonotic transmission.